Syndicats : lendemains de crise ? - Gagnon, Mona-Josée (Relations industrielles / Industrial Relations, 2006)
The article reviews the book, "Syndicats : lendemains de crise ?," by Jean-Marie Pernot.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z